Economic Financial and Sustainability Drivers of Firm Value: The Moderating Role of Dividends in Southeast Asia’s Oil, Gas, and Lubricant Sector (2021–2024) - Agnes Prety Sinta Yuliana; Marhaendra Kusuma; Miladiah Kusumaningarti (International Journal of Economics Development Research (IJEDR), 2025)
This study examines the economic influence of financial performance and sustainability performance on firm value, with dividends serving as a moderating variable, in oil, gas, and lubricant sub-sector companies across Southeast Asia during the 2021–2024 period. A quantitative causal research design was employed, utilizing secondary data derived from annual and sustainability reports of publicly listed companies in Southeast Asian stock exchanges. The sample comprises 18 companies selected through purposive sampling. The variables analyzed include financial performance (Return on Assets/ROA), sustainability performance (Environmental, Social, and Governance/ESG Score based on the 2021 GRI Standards), firm value (Price to Book Value/PBV), and dividends as a moderating variable. Data were analyzed using Moderated Regression Analysis (MRA) with SPSS version 26. The findings reveal that financial performance initially shows no significant effect on firm value; however, after the inclusion of dividends as a moderating variable, the effect becomes significant and negative. Sustainability performance (ESG Score) demonstrates a positive and significant influence on firm value before moderation, but this relationship loses significance once dividends are introduced into the model. Furthermore, dividends do not moderate the relationship between financial performance and firm value, yet they significantly and negatively moderate the relationship between sustainability performance and firm value. This suggests that higher dividend payouts may weaken the positive impact of sustainability performance on firm value, as investors tend to prioritize short-term returns over long-term sustainability benefits. These results imply that companies should carefully align dividend policies with sustainability strategies to sustain long-term firm value and investor confidence.